Research on control strategy of two-stage photovoltaic virtual synchronous generator with variable power point tracking - Bo Zhang (Elsevier, 2022)
Based on the analysis of the operation characteristics of photovoltaic cells, a novel virtual synchronous generator adaptive power regulation strategy for two-stage three-phase photovoltaic system with high permeability of clean energy is proposed. By improving the maximum power point tracking process of photovoltaic cells, the variable power point tracking control of photovoltaic cells is realized, and the control effect of DC/DC converter on the output power of photovoltaic cells is fully exerted. Without additional energy storage equipment, the energy supply required for inertia support and primary regulation of virtual synchronous generator is accurately realized. Combined with inverter VSG control strategy, the control of photovoltaic virtual synchronous generator is realized.